Filaggrin gene variants among Saudi patients with ichthyosis vulgaris - Omar Mohammed Alakloby; Fatimah Almuqarrab; Johannes Zschocke; Mathias Schmuth; Adnan Abdulkareem; Kholood Alnutaifi; Francis Borgio; Robert Gruber; Hans Christian Hennies (BMC, 2023)
Abstract Ichthyoses are a heterogeneous group of cornification disorders. The most common form of ichthyoses is ichthyosis vulgaris (IV) ([OMIM] #146,700), which can be inherited as autosomal semi-dominant mutation in the filaggrin gene (FLG). We present the findings of a study involving 35 Saudi patients with a clinical diagnosis of ichthyosis vulgaris. For identifying the pathogenic mutation of their disease, we used Sanger sequencing analysis of the extracted DNA samples. We also identified the underlying 22 FLG variants, which have been seen before. However, the detected mutations do not involve the common p.R501* c. 2282del4 mutations reported in European populations. Indeed, we did not identify any statistical influence of the homozygous or heterozygous genotypes on the phenotype severity of the disease.